The Forest Dynamics of Carbon Sequestration and Some Environmental Factors Influencing the Distribution of Tree Species in the Royal-Instated Mae-Aow River Basin Development Project, Lamphun Province - Tamniyom, Sumet; Hermhuk, Sutheera; Kamyo, Torlarp; Ponpituk, Yuwadee (KKU Science Journal, 2026)
Understanding forest dynamics after natural forest restoration and the environmental factors influencing tree species distribution is essential for elucidating successional processes and developing strategies to accelerate each tree species for forest recovery. This study investigated changes in dynamics of forest composition, biomass carbon storage, and key environmental drivers of dominant tree species distribution in naturally recovery mixed deciduous forest (MDF) and deciduous dipterocarp forest (DDF) in Pa Sang District, Lamphun Province. Three permanent plots of 20 m x 50 m were established in each forest type. Topographic data and soil samples were collected for laboratory analysis, while tree growth was monitored in 2020, 2022, and 2024. A total 68 species, 58 genera and 29 families were found, with a moderate mean Shannon-Wiener diversity index (H’ = 2.23 ± 0.52). Species dominance varied by forest type: Dipterocarpus tuberculatus in DDF and Millettia leucantha var. buteoides in MDF. Forest dynamics showed increases from year 2020 and 2022 increases in basal area of 0.37 and 1.41 m2. Mortality rate (3.01%) recruitment rate (1.53%) in 2022, whereas the second period 2024, the recruitment rate (4.92%) was higher than the mortality rate (3.42%). In terms of carbon storage in biomass, in 2024, the total forest biomass accumulation was 54.72 tons, equivalent to 32.66 tons of carbon storage in biomass. However, overall carbon storage declined by 7.63 tons equivalent to 4.06 tons per rai, over four years due to high mortality rate. The identification of factors indicated that the elevation and silt strongly influenced MDF, while sand, clay and soil chemical such potassium and calcium factors shaped DDF. These findings found the dynamic of natural forest restoration, mortality and recruitment rate and site factors in determine the potential of carbon storage and tree species distribution. They provide a basis for refining restoration strategies to enhance forest recovery and carbon storage in forest ecosystems.